2014
DOI: 10.1017/ice.2014.27
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Parenteral Antimicrobial Therapy in Pediatrics: An Opportunity to Expand Antimicrobial Stewardship

Abstract: We reviewed patient discharges with outpatient parenteral antimicrobial therapy (OPAT) to determine whether outpatient parenteral antimicrobial therapy was modifiable or unnecessary at a large tertiary care children's hospital. At least one modification definitely or possibly would have been recommended for 78% of episodes. For more than 40% of episodes, outpatient parenteral antimicrobial therapy was potentially not indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…There is a growing recognition that OPAT is overused and that overuse can be minimized through antimicrobial stewardship. 21,22 This is supported by an expanding evidence base indicating that the effectiveness of oral therapy is equivalent to OPAT for a variety of serious pediatric infections frequently treated with OPAT, including complicated appendicitis and osteomyelitis. [23][24][25][26] In a recent study comparing oral therapy with OPAT for osteomyelitis, rates of treatment failure were similar between groups.…”
Section: Discussionmentioning
confidence: 97%
“…There is a growing recognition that OPAT is overused and that overuse can be minimized through antimicrobial stewardship. 21,22 This is supported by an expanding evidence base indicating that the effectiveness of oral therapy is equivalent to OPAT for a variety of serious pediatric infections frequently treated with OPAT, including complicated appendicitis and osteomyelitis. [23][24][25][26] In a recent study comparing oral therapy with OPAT for osteomyelitis, rates of treatment failure were similar between groups.…”
Section: Discussionmentioning
confidence: 97%
“…Clinicians often fail to provide adequate patient oversight7; Hodgson et al identified that 26% of their paediatric OPAT patients received an incorrect dose, route or duration of antibiotics and an inappropriate indication for treatment was cited in 6% 8. Overall, drug-related and line-related complications are reported to occur in 20% to 30% of paediatric OPAT patients, correlating with increasing intravenous therapy durations 4 9–12…”
Section: Introductionmentioning
confidence: 99%
“…For example, ASPs can focus on children being discharged to undergo outpatient parenteral antimicrobial therapy (OPAT). Overuse of OPAT exposes patients to complications such as catheter-associated infections and thrombosis, and OPAT can be avoided in some children in favor of oral therapy for infections such as osteomyelitis [32,42,43]. Similarly, investigating and removing unnecessary β-lactam allergy labels represents an opportunity for ASPs to direct patients toward first-line, generally more narrow-spectrum, agents [44,45].…”
Section: Extending Asp Strategies To New Target Areas and Populationsmentioning
confidence: 99%